Settlements of the Serbian Župa/Ottoman nahiye of Topolnica (15th-16th century) - Katić Tatjana M. (Baština, 2024)
Since the time of Konstantin Jireček and Stojan Novaković, the Serbian medieval county (župa) of Topolnica, well-known as Anđelova Topolnica, has been incorrectly identified with the area of Kriva Reka in the Novo Brdo region. The scanty medieval sources do not provide sufficient data to reconstruct the župa's territory or the number and names of its settlements. The mentions of Topolnica's villages, churches, and monasteries appear more numerous only in the second half of the 15th and 16th centuries in Ottoman sources - tapu tahrir defters. Namely, the Ottoman state, which almost entirely adopted the medieval organization of counties, replacing only the term župa with the term nahiye, regularly carried out the censuses of settlements and populations throughout the Empire, including the Topolnica county that belonged to the Vučitrn sanjak. Based on the data on Topolnica settlements in the Vučitrn tapu tahrir defters, it is possible to determine the scope of the medieval župa, i.e., the early modern nahiye of Topolnica. So far, only the incomplete census from 1455, containing Topolnica's 54 active villages, eight abandoned villages, and two monasteries, has been published. A significant part of these settlements was successfully identified, but there are also a number of misidentified or untraceable ones. The aim of this paper, based on several unpublished and underused Ottoman censuses from the 15th and 16th centuries, is to correct the position of thus far inappropriately located settlements and to show that the county of Topolnica included about 120 settlements, none of which were situated in the medieval area of Kriva Reka. The Ottoman defters also reveal that Anđelova Topolnica was the name of a particular settlement, not the entire county. At the beginning the settlement was called the village of Angeli after the Byzantine family of Angeli, who ruled Thessaly in the 14th century and who, after the Ottoman conquest, settled in Serbia and got estates. Their landholdings were located near the existing village of Topolnica, with which they soon merged and which began to be called Angeli's Topolnica or Anđelova Topolnica.